Kebijakan Transformatif Kerjasama Dan Share Value - Widhyharto, Derajad S. (Jurnal Kebijakan Publik, 2012)
This study describes the relevanceof the policy in order to make transformative change through the process of cooperation andshared values in Batam City, Riau Islands Province. This study used qualitative methods, thecase study where the researcher acts as the main instrument. All data and information collectedare recorded in the notes, and then grouped according to the needs. Further written narrativeassociated with the theory and reasoning researchers themselves. Results showed industrialsettings in Batam planting expected to encourage social relationships harmonious, in fact underthe concept of industrial settings such situation is reversed, ie social relations defined by relations-industrial economy.